Summarizing the theoretical foundation for hospital communication research: A scoping review of interdisciplinary literature. - Keeppanasseril, Arun (My University, 2012)
Hospitals are complex socio-technical systems where health professionals from varied backgrounds interact with each other and technology for the wellbeing of patients. Effective communication among the members of the care team is vital for optimal care; poor communication can result in suboptimal care and in many cases, lead to adverse events (AEs) and even death. More than a decade after the US Institute of Medicine report which catalyzed patient safety improvement measures, patient safety remains a major concern. Two-thirds of AEs in hospitals are still linked to communication errors. Hospitals are trying to improve communication by introducing new communication devices like smart phones and tablet computers for professional use. However, they are being deployed without adequate study of the mechanics of communication in hospitals or their use affects inter-professional communication. High risk organizations such as nuclear power plants, aviation and the military have achieved better safety records than healthcare. This is likely because they have studied their communication challenges and based their assessments on a firm theoretical foundation before implementing customized solutions. This approach in healthcare is lacking. Therefore a scoping review was conducted to collect communication theories, models, frameworks, and methods applicable to new information and communication technology used in hospitals. Literature from basic and applied science domains such as cognitive psychology, human factors engineering, organizational behavior, sociology, communication sciences and from high risk organizations like aviation, nuclear power generation and defense was reviewed. 14 theories, 12 models and 12 communication analysis methods were identified. One of the selected methods was employed to conduct a case study of a case of faulty communication reported in the AHRQ web M&M. It is not known how well those theories, models and analysis methods can be adapted to medicine. Future research may be able to address the issue and adopt theories and models to hospital communication research, modifying existing theories and models to suit the unique requirements of hospitals or by developing a strategy to design them de-novo.
Keywords: Hospital Communication; Nuclear Power Generation; Communication theory; Communication Model; Knowledge Translation; Knowledge Translation